DG Dr. Nteranya Sanginga's Speech at International Women's Day 2019 - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2019)
IITA Director General Dr Nteranya Sanginga's Speech on the occasion of International Women's Day 2019. #Balanceforbetter #IWD Think Equal, Build Smart, Innovate for Change.